Associations Between Ambient Temperature and Circulating Maternal One-carbon and Amino Acid Metabolites in Pregnancy. (14th June 2022) - Shankar, Kartik; Borengasser, Sarah; Ali, Sumera; Jessani, Saleem; Gilley, Stephanie; Kemp, Jennifer; Jambal, Puujee; Westcott, Jamie; Saleem, Sarah; Goldenberg, Robert; Hambidge, Michael; Krebs, Nancy
Abstract: Objectives: Excessive ambient temperature closely linked to climate change is an imminent threat to the health of mothers and children globally. Recent studies have shown detrimental associations between high temperatures during pregnancy and birth outcomes. The goal of this study was to examine relationships between circulating metabolites in the mother and environmental temperature in a resource-limited setting. Methods: The study was a secondary analysis employing data from the Women First (WF) trial conduced in Thatta, Pakistan. As part of the trial, women of child-bearing age either consumed a comprehensive maternal nutritional supplement (MNS) prior to conception until delivery (Arm 1), from 12 wk gestation until delivery (Arm 2); or were not supplemented with MNS Arm 3. Daily maximum air temperatures were acquired from the closest surface observation systems (n = 131). Average daily maximum temperatures (Tmax ) for a 90-day window representing the 1 st trimester of pregnancy was calculated for each participant. The number of days in this period when the Tmax was > 39°C was computed to assess 'heat stress days'. Maternal blood was collected on dried blood spot (DBS) cards at 34 wk gestation. A targeted metabolomics assay measuring concentrations of 23 metabolites was performed on DBS samples using LC-MS/MS. Results: Linear regression was employed to assess the associations between ambient temperature in the 1 st trimester and metabolite levels (z-scores). Models were adjusted for MNS supplementation. Significant associations between Tmax in the 1 st trimester and 7 metabolites were observed (FDR p -values < 0.05). Of these, maternal choline concentrations were negatively correlated with maximal temperature in the 1 st trimester (β = −0.063, p  = 4.3e-10). Concentrations of glutamine, histidine, arginine, symmetrical-dimethylarginine, methionine and cysteine were positively associated ( p < 0.05) with daily maximal temperature. Conclusions: Collectively, the findings indicate that exposure to excessive heat stress in the first trimester is associated with lower choline levels and other metabolites important in blood pressure regulation. While the findings are associative, our results point to underlying mechanistic alterations in maternal circulation in concert with environmental heat stress. Funding Sources: Bill & Melinda Gates Foundation; NIH/NICHD/ODS.